Anti-crisis measures in the republic of Macedonia and their effects: Are they sufficient? - Abdulmenaf Bexheti (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2010)
Macedonia's economy was not left behind by the global economic crisis as the country's macroeconomic policymakers had hoped! Certainly, an economy open at all and with a high degree of direct dependence on European and global economies in general should not be saved by the crisis in financial top and then the global economic. Transmission of negative effects but came a little late economic shocks in the periphery are often stronger than the epicenter. In these circumstances macroeconomic policymakers should be more proactive, coherent and dynamic design of the following measures and economic policies increasingly based on relevant research and analysis (decision making based on research and analysis). Therefore, this analysis aims to develop and study in detail the measures in terms of economy, Science and Technology of Macedonia in order to suggest a more effective policy in accordance with business cycles, always comparing the economic measures in other states with which the country has advanced reports on economic but referring to specific local economic conditions. Accordingly the specific activities recommended for further action.
Keywords: G28; H30; H60; H70; 330; Financial Crisis; Anti-crisis Measures; Cyclic Regulated Fiscal Policy; Budget Deficit and Public Debt; Finanzmarktkrise; Wirtschaftskrise; Wirtschaftspolitik; Antizyklische Finanzpolitik; Mazedonien